Ammonium, nitrate and phytoplankton interactions in a freshwater tidal estuarine zone: potential effects of cultural eutrophication - Domingues, Rita B. (2012)
Nitrate and ammonium are the most important nitrogen sources for phytoplankton growth. Differential utilization of inorganic nitrogenous compounds by phytoplankton has been observed and may have significant impacts on primary productivity at local scales. We used enrichment experiments with natural phytoplankton populations from the freshwater tidal zone of the Guadiana estuary, a coastal ecosystem increasingly subjected to anthropogenic influences, to study the effects of nitrate and ammonium on N-consumption and phytoplankton growth. In addition, we used combined additions of nitrate and ammonium to understand the inhibitory effect of ammonium over nitrate uptake. Ammonium concentrations in the freshwater tidal reaches of the Guadiana estuary throughout the sampling period were too low to exert an inhibitory effect on nitrate uptake or a toxic effect on phytoplankton growth. Nitrate was clearly the main nitrogen source for phytoplankton at the study site. Overall, nitrate seemed to become limiting at concentrations lower than 20 lM and N-limitation was particularly significant during summer. A trend of decreasing nitrate uptake with increasing ammonium concentrations and uptake suggested an overall preference for ammonium. However, preference for ammonium was group-specific, and it was observed mainly in green algae and cyanobacteria. In fact, cyanobacteria relied only on ammonium as their N-source. On the contrary, diatoms preferred nitrate, and did not respond to ammonium additions. The increasing eutrophication in the Guadiana estuary and particularly increased inputs of nitrogen as ammonium due to urban waste effluents may result in a shift in phytoplankton community composition, towards a dominance of cyanobacteria and green algae.